2021
DOI: 10.1097/mat.0000000000001557
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of an Early Mobilization Protocol for Patients with Femoral Intra-Aortic Balloon Pumps as Bridge to Heart Transplant

Abstract: Intra-aortic balloon pumps (IABPs) can be used to provide hemodynamic support in patients with end-stage heart failure as a bridge to transplantation (BTT). The IABP is commonly inserted via the common femoral artery, which can limit patients’ mobility. The Ramsey protocol, developed by a critical care physical therapist, allows patients with femoral IABPs to ambulate with the assistance of a tilt table. The aim of this study was to determine the safety and feasibility of a modified Ramsey protocol for early m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
0
15
0
3
Order By: Relevance
“…Although two prior, single-center experiences prove feasibility and safety ambulating these patients, our experience extends these data with longer support periods, more ambulation sessions and further walk distances during these sessions. 5,6 Prolonged bed rest has multiple deleterious effects on muscle mass, bone mineral density, and the cardiovascular system, and these effects are magnified by critical illnesses and ambulation with a femoral IABP may counteract theses deleterious outcomes. 7 Our simplified ambulation process, allowing patients to walk with an unrestricted, natural gait, decreases necessary resources to ambulate these patients and will allow other centers to more easily replicate our experience (Supplemental Digital Content 3, http://links.lww.com/ASAIO/B20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although two prior, single-center experiences prove feasibility and safety ambulating these patients, our experience extends these data with longer support periods, more ambulation sessions and further walk distances during these sessions. 5,6 Prolonged bed rest has multiple deleterious effects on muscle mass, bone mineral density, and the cardiovascular system, and these effects are magnified by critical illnesses and ambulation with a femoral IABP may counteract theses deleterious outcomes. 7 Our simplified ambulation process, allowing patients to walk with an unrestricted, natural gait, decreases necessary resources to ambulate these patients and will allow other centers to more easily replicate our experience (Supplemental Digital Content 3, http://links.lww.com/ASAIO/B20).…”
Section: Discussionmentioning
confidence: 99%
“…4 Preliminary experience from two centers using similar protocol showed that ambulation of such patients is both safe and feasible. 5,6 Accordingly, we undertook ambulation of patients with femoral IABP while awaiting heart transplantation at our center. Herein, we report our experience with ambulation of patients with a novel nonrestrictive ambulation protocol which facilitated greater ambulation distances, increased patient satisfaction and required fewer resources.…”
mentioning
confidence: 99%
“…However, with meticulous nursing care and physiotherapy, these risks can be mitigated, and this case therefore demonstrates that the femoral IABP can be safely and effectively used for longer term support if necessary. Such approaches may become more common with the development of novel mobilisation protocols for patients supported with femoral IABPs 5 which will permit more intensive physiotherapy and may therefore improve bridging efficacy and post-transplant outcomes.…”
mentioning
confidence: 99%
“…Emerging literature shows that mobilization of patients with a femoral IABP is safe and feasible 26–28. Ramsey et al26 published a protocol to guide mobilization of patients with a femoral IABP.…”
mentioning
confidence: 99%
“…Emerging literature shows that mobilization of patients with a femoral IABP is safe and feasible. [26][27][28] Ramsey et al 26 published a protocol to guide mobilization of patients with a femoral IABP. We appreciated how this protocol described techniques on how to mobilize patients with a femoral IABP and was organized by phase of mobility.…”
mentioning
confidence: 99%